FACILITIES AND ACHIEVEMENTS OF INCLUSIVE EDUCATION - Uzoqjonova Moxinur Diyorbek qizi (PEDAGOGS, 2024)
Abstract: This article provides a brief overview of inclusive education. The benefits of inclusive education and the achievements are briefly highlighted, the goals and objectives of inclusive education, and their impact on the effectiveness of the “Law on Inclusive Education” are given.